Dissecting mechanisms of chromosomemicrotubule interaction in oocytes by new imaging tools - Gluszek, Agnieszka Agata; Głuszek-Kustusz, Agnieszka Agata (The University of Edinburgh, 2014)
Chromosome alignment and orientation within the spindle in mitosis and meiosis are determined by chromosome-microtubule interaction. Evidence suggests that within the acentrosomal spindle the mechanism of chromosome positioning is different from in mitotic spindle but its molecular bases are not well understood. I investigated how chromosome-microtubule interactions position the chromosomes within the spindle using Drosophila oocytes. I addressed the role and molecular mechanisms of kinetochore and chromosome interaction with microtubules in this process. I developed new live imaging reagents to observe dynamic chromosome-microtubule interaction. Live imaging combined with inactivation of kinetochores in oocytes revealed that kinetochore-microtubule attachment is required for three-step chromosome positioning in Drosophila oocytes: de-congression, change of orientation and re-congression. Augmin, a γ-tubulin recruiting complex, has been previously shown to be important for chromosome congression specifically in oocytes. Live imaging further showed that Augmin facilitates chromosome congression particularly in early stages of spindle assembly. Study of Augmin dynamics revealed that Augmin stably associates with spindle polar regions, specifically in oocytes. This meiotic regulation of Augmin function may contribute to generation of force pushing chromosomes toward spindle equator. Sentin protein has been shown to be important for microtubule plus end dynamics in mitosis. In meiosis, sentin mutant results in reduced distance between centromeres of homologous chromosomes. However, its meiotic role is unknown. Live imaging of the sentin mutant showed that in oocytes Sentin is required for preventing premature stabilization of kinetochore-microtubule attachments. As conclusion, I have used live imaging to reveal molecular basis of the interaction between chromosomes and microtubules particularly important for oocytes.
Keywords: kinetochore; spindle; oocytes